Structural Influence of Digital Marketing Strategies on Purchase Decisions of FMCG Products in Salem District - P. Selvi,; Dr. R. Brinda Shree, (IJRDO - Journal of Business Management, 2025)
The increasing penetration of digital technologies has transformed the marketing landscape of the FMCG sector shifting traditional advertising practices toward more personalised and interactive approaches. The objectives of the study were twofold: to examine the structural impacts of digital marketing dimensions such as personalisation, content relevance, platform interactivity and influencer credibility in shaping cognitive influence on FMCG purchases and to evaluate how personalised digital marketing techniques affect consumer trust, which in turn strengthens purchase behaviour. An empirical research design was adopted, and primary data were collected through a structured interview schedule administered to consumers across top FMCG categories in Salem District. A snowball sampling method was employed to identify respondents, and the data were analysed using a combination of ANOVA and SEM with path analysis. The model tested the interrelationships between digital marketing dimensions, cognitive influence, consumer trust and purchasing habits. The findings revealed that personalisation quality exerted the strongest influence on cognitive processing followed by content relevance and platform interactivity while influencer credibility played a supportive but less decisive role. Cognitive influence emerged as the key mediator linking digital marketing efforts to consumer purchase behaviour. This research contributes to the theoretical understanding of digital marketing effectiveness in the FMCG sector by emphasising cognition and trust as central pathways between marketing strategies and consumer behaviour.